The role of macrophage and adipocyte mitochondrial dysfunction in the pathogenesis of obesity - Wang, Min; Min, Min; Duan, Haojie; Mai, Jia; Liu, Xiaojuan (Frontiers in Immunology, 2024)
Obesity has emerged as a prominent global public health concern, leading to the development of numerous metabolic disorders such as cardiovascular diseases, type−2 diabetes mellitus (T2DM), sleep apnea and several system diseases. It is widely recognized that obesity is characterized by a state of inflammation, with immune cells-particularly macrophages-playing a significant role in its pathogenesis through the production of inflammatory cytokines and activation of corresponding pathways. In addition to their immune functions, macrophages have also been implicated in lipogenesis. Additionally, the mitochondrial disorders existed in macrophages commonly, leading to decreased heat production. Meantime, adipocytes have mitochondrial dysfunction and damage which affect thermogenesis and insulin resistance. Therefore, enhancing our comprehension of the role of macrophages and mitochondrial dysfunction in both macrophages and adipose tissue will facilitate the identification of potential therapeutic targets for addressing this condition.